Identification of phase transitions and metastability in dynamically compressed antimony using ultrafast x-ray diffraction - Coleman, AL; Gorman, MG; Briggs, R; McWilliams, RS; McGonegle, D; Bolme, CA; Gleason, AE; Fratanduono, DE; Smith, RF; Galtier, E; Lee, HJ; Nagler, B; et al. (American Physical Society, 2019)
Ultrafast x-ray diffraction at the LCLS x-ray free electron laser has been used to resolve the structural behavior of antimony under shock compression to 59 GPa. Antimony is seen to transform to the incommensurate, host-guest phase Sb-II at ∼11 GPa, which forms on nanosecond timescales with ordered guest-atom chains. The high-pressure bcc phase Sb-III is observed above ∼15 GPa, some 8 GPa lower than in static compression studies, and mixed Sb-III/liquid diffraction are obtained between 38 and 59 GPa. An additional phase which does not exist under static compression, Sb-I', is also observed between 8 and 12 GPa, beyond the normal stability field of Sb-I, and resembles Sb-I with a resolved Peierls distortion. The incommensurate Sb-II high-pressure phase can be recovered metastably on release to ambient pressure, where it is stable for more than 10 ns.